How researchers perceive research misconduct in biomedicine and how they would prevent it: A qualitative study in a small scientific community. (19th May 2018) - Buljan, Ivan; Barać, Lana; Marušić, Ana
ABSTRACT: The aim of our study has been to use a qualitative approach to explore the potential motivations and drivers for unethical behaviors in biomedicine and determine the role of institutions regarding those issues in a small scientific community setting. Three focus groups were held—two with doctoral students and one with active senior researchers. Purposive sampling was used to reach participants at different stages of their scientific careers. Participants in all three focus groups were asked the same questions regarding the characteristics and behaviors of ethical/unethical scientists, ethical climate, role, and responsibility of institutions; they were also asked to suggest ways to improve research integrity. The data analysis included coding of the transcripts, categorization of the initial codes, and identification of themes and patterns. Three main topics were derived from the focus groups discussions. The first included different forms of unethical behaviors including increasing research "waste, " non-publication of negative results, authorship manipulation, data manipulation, and repression of collaborators. The second addressed the factors influencing unethical behavior, both external and internal, to the researchers. Two different definitions of ethics in science emerged; one from the categorical perspective and the other from the dimensional perspective. The third topic involved possible routes for improvement, one from within the institution through the research integrity education, research integrity bodies, and quality control, and the other from outside the institution through external supervision of institutions. Based on the results of our study, research misconduct in a small scientific community is perceived to be the consequence of the interaction of several social and psychological factors, both general and specific, for small research communities. Possible improvements should be systematic, aiming both for improvements in work environment and personal awareness in research ethics, and the implementation of those changes should be institutional responsibility.